If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -3) + -1(-3x + 2) = 0 Reorder the terms: (-3 + 6x) + -1(-3x + 2) = 0 Remove parenthesis around (-3 + 6x) -3 + 6x + -1(-3x + 2) = 0 Reorder the terms: -3 + 6x + -1(2 + -3x) = 0 -3 + 6x + (2 * -1 + -3x * -1) = 0 -3 + 6x + (-2 + 3x) = 0 Reorder the terms: -3 + -2 + 6x + 3x = 0 Combine like terms: -3 + -2 = -5 -5 + 6x + 3x = 0 Combine like terms: 6x + 3x = 9x -5 + 9x = 0 Solving -5 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 9x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 9x = 0 + 5 9x = 0 + 5 Combine like terms: 0 + 5 = 5 9x = 5 Divide each side by '9'. x = 0.5555555556 Simplifying x = 0.5555555556
| 3(x-2)=-(6-x) | | 1.5x=1.3x+4 | | 1/4(x-8)1/12= | | 13-5x=-5 | | -6x+30+2x-20-4x+30= | | 5x-9+7x=-21 | | 12-3x+4=-2x+7+8x | | -6x+30+2x-20-4x+30x= | | 3/4(x)=23 | | 41+10x=101 | | 3/4(x)=55 | | 3x+9+2x=-36 | | 2/3(x)=55 | | 2(y+1)=10 | | 6.4=0.4r | | 50-4y=4 | | 4x+30-6x+40=-6x+3+5x-25 | | -9(x+7)+5=-58 | | 9x-(6x-3)=27 | | 9999999+9999999999= | | -2=-8+7x-8x | | 4×3/4= | | 5=n-1/3 | | 5(x+2)=7x+10-2x | | 2(5r-9)-4(4r+3)= | | v^2-7v+14=4 | | -3(x+6)-43=7-47 | | 24x+6-27x=4-7 | | 45=2x+27 | | x/-6=-4-(-5) | | x+(-13)=2 | | 50-4t-4.9t^2=0 |